Tanshinone IIA Inhibits High Glucose-Induced Collagen Synthesis via Nuclear Factor Erythroid 2-Related Factor 2 in Cardiac Fibroblasts - Yi-Ting Tsai; Shih-Hurng Loh; Chung-Yi Lee; Shiao-Ping Lee; Yen-Lin Chen; Tzu-Hurng Cheng; Chien-Sung Tsai (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Diabetes is associated with increased incidence of myocardial dysfunction, which is partly characterized by interstitial and perivascular fibrosis. Cardiac fibroblasts have been identified as an important participant in the development of cardiac fibrosis. Exposure of cultured cardiac fibroblasts to high glucose resulted in increased collagen synthesis. Tanshinone IIA can alleviate the ventricular fibrosis that develops in a number of different experimental conditions. However, whether tanshinone IIA can prevent high glucose-induced collagen synthesis in cardiac fibroblasts remains unknown. The aim of this study was to evaluate the effects of tanshinone IIA on high glucose-induced collagen synthesis in cardiac fibroblasts. Methods: Rat cardiac fibroblasts were cultured in high glucose (25 mM) media in the absence or presence of tanshinone IIA and the changes in collagen synthesis, transforming growth factor-β1 (TGF-β1) production and related signaling molecules were assessed by 3H-proline incorporation, quantitative polymerase chain reaction, enzyme linked immunosorbent assay, and Western blotting. Results: The results indicate cardiac fibroblasts exposed to high glucose condition show increased cell proliferation and collagen synthesis and these effects were abolished by tanshinone IIA treatment. Furthermore, the inhibitory effect of tanshinone IIA on high glucose induced cell proliferation and collagen synthesis may be associated with its activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) and the inhibition of TGF-β1 production and Smad2/3 phosphorylation. Conclusion: In summary, our results highlights the critical role tanshinone IIA plays as an antioxidant in attenuating high glucose-mediated collagen synthesis through inhibiting TGF-β1/Smad signaling in cardiac fibroblasts which provide a mechanistic basis for the clinical application of tanshinone IIA in the treating diabetic-related cardiac fibrosis.